STRATEGI PEMBELAJARAN MATEMATIKA MENYENANGKAN SISWA (MMS) BERBASIS METODE PERMAINAN MATHEMAGIC, TEKA-TEKI DAN CERITA MATEMATIS - Maswar Maswar (Fakultas Tarbiyah Universitas Ibrahimy, 2019)
Until now there are still many students who consider aboaut metematics as a school subject that is considered scary and boring. Because it contains many difficult and meticulous formulas. Though mathematics is a very important subject to be learned along with the progress of Science and Technology increasingly sophisticated in Era 4.0. Through Mathematics with all its applications, it creates many kinds of increasingly sophisticated contemporary technologies. Mathematics can be said to be the mother of all sciences. Therefore, mathematics is very important to be taught to students and must be able to be well received and enjoyable. Therefore it is necessary to look for a development of mathematical learning concepts that are in accordance with the characteristics of students namely fun mathematics learning strategies that can make students happy when studying, both at school and at private institutions. In this paper discusses focused for fun learning strategies based on mathematical game methods, Mathematical Puzzles, and Mathematical Stories.